THE EFFECT OF HALAL LABEL, PRODUCT QUALITY AND PRICE ON CUSTOMER SATISFACTION WARDAH COSMETICS - Mirza Astia Amri; Asiah Hasibuan (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the effect of the halal label, product quality, and price on consumer satisfaction with wardah cosmetics. The method used is a quantitative approach method with multiple regression data analysis using independent variables including halal labels, product quality and prices that affect the dependent variable, namely consumer satisfaction with a total sample of 32 respondents. The results of the analysis stated that the halal label had an effect of 24.3% on customer satisfaction, product quality had an effect of 34.1% on satisfaction and price had no effect on satisfaction with a value of -9.84%.